Comparative study of Ziehl-Neelsen (Z-N) Staining Versus Fluorochrome Stain for Pulmonary Tuberculosis (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Tuberculosis is a highly infectious disease and has the highest burden with it. Diagnosis of tuberculosis in many countries is still dependent on microscopy. For developing countries with a large number of cases and financial constraints, evaluation of rapid and inexpensive diagnostic methods has great importance. The bacilli in the sputum can be detected microscopically by ZN stain and fluorochrome stain.Objective: The purpose of the present study was to compare the efficacy of flurochrome(FI) stain with Z-N stain in the diagnosis of pulmonary tuberculosis.Methodology: This cross sectional study was done in the Department of Microbiology at Sir Salimullah Medical College, Dhaka and National Institute of Chest Disease & Hospital (NIDCH), Dhaka during the period of January 2014 to December 2015 for a period of 1(one) year. Sputum samples from suspected MDR-TB patients were collected by purposive sampling technique from OPD of Sir Salimullah Medical College (SSMC) and NIDCH. Microscopy, liquid culture in liquid MGIT 960 media were done for MTB diagnosis.Result: this study shows the comparison of results of microscopic examination of Fluorochrome and Z-N stained sputum smear. Both Fluorochrome and Ziehl-Neelsen stains showed predominant positive results, that is, 3+ in 50% and 50.94% samples respectively, followed by 2+ in 30.65% and 32.07% samples, 1+ in 14.5% and 13.2% samples and scanty in 4.84% and 3.77% samples respectively. On the other hand, Fluorochrome stain gave negative report in 38 (38%) samples, whereas Z-N staining showed 47 (47%) negative results.Conclusion: Fluorochrome stain yielded more positive result than Z-N stain under microscope in smear of sputum.J Shaheed Suhrawardy Med Coll, June 2018, Vol.10(1); 28-30